TEACHER CREATIVITY IN INCREASING STUDENT INTEREST IN LEARNING ARABIC CLASS VII SMPIT INSAN KAMIL CIKARANG - Prasetyo, Dimas (Program Studi Pendidikan Bahasa Arab, 2024)
In the context of learning, there are various supporting factors that can encourage students to learn, and one of them is interest. Interest is an internal drive that can trigger interest or attention effectively. Students who have a high interest can be expected to achieve optimal learning achievement. The role of a teacher has a significant impact on fostering students' interest in learning. To achieve educational targets, a teacher who is professional, creative, and able to create a pleasant learning environment is needed. This study aims to evaluate teacher creativity in increasing the interest in learning of grade VII students at SMPIT Insan Kamil Cikarang. The research method used is qualitative with a phenomenological approach. This study utilized several data collection techniques, including observation, interviews, questionnaires, and documentation. Data analysis techniques refer to the Huberman Model, which involves data collection, data reduction, data presentation, and conclusions. The results showed that the interest in learning Arabic for grade VII students at SMP IT Insan Kamil was relatively high, with 73.5% or 75 out of 98 students showing fondness for Arabic based on the results of the questionnaire. The conclusion that can be drawn is that the creativity of Arabic teachers in class VII of SMP IT Insan Kamil is more inclined towards creativity in classroom management